Increased Reward-Related Activation in the Ventral Striatum During Stress Exposure Associated With Positive Affect in the Daily Life of Young Adults With a Family History of Depression. Preliminary Findings - Martin-Soelch, Chantal; Guillod, Matthias; Gaillard, Claudie; Recabarren, Romina Evelyn; Federspiel, Andrea; Mueller-Pfeiffer, Christoph; Homan, Philipp; Hasler, Gregor; Schoebi, Dominik; Horsch, Antje; Gomez, Patrick (Frontiers in Psychiatry, 2021)
Being the offspring of a parent with MDD is a strong predictor for developing major depression disorder (MDD). Blunted striatal responses to reward were identified in individuals with MDD and in asymptomatic individuals with family history of depression (FHD). Stress is a major etiological factor for MDD and was also reported to reduce the striatal responses to reward, but the stress-reward interactions in FHD individuals has not been explored yet. Extending neuroimaging results into daily-life experience, self-reported ambulatory measures of positive affect (PA) were shown to be associated with striatal activation during reward processing. A reduction of self-reported PA in daily life is consistently reported in individuals with current MDD. Here, we aimed to test 1) whether acute stress administration differently affect striatal responses in a control group and in an asymptomatic FHD group; 2) whether the FHD group would show reduced self-reported daily life PA measures; and 3) whether the association between self-reported PA and the striatal activation to reward (with and without stress) is different in the two groups. Method Participants were 16 asymptomatic young adults with FHD and 16 controls (HC). They performed the Fribourg Reward Taskwith and without stress induction, using event-related fMRI. We conducted whole-brain analyses comparing the two groups for the main effect of reward (rewarded > not-rewarded) during reward feedback in control (no-stress) and stress conditions. Beta weights extracted from significant activation in this contrast were correlated with self-reported PA and negative affect (NA) assessed over one week. Results Under stress induction, the reward-related activation in the ventral striatum (VS) was higher in the FHD group than in the HC group. During stress induction, VS reward-related activation correlated positively with PA in both groups and negatively with NA in the HC group. Conclusion As expected, our results indicate that increased family risk of depression was associated with specific striatum reactivity to reward in a stress condition, and support previous findings that ventral striatal reward-related response is associated with PA. A new finding is the negative association between NA and reward-related ventral striatal activation in the HC group.